SOIL CHARACTERISTICS OF SIX MANAGEMENT REGIMES IN LOMBOK INDONESIA - Sitti Latifah; Eni Hidayati; Niechi Valentino (Jurnal Belantara, 2022)
A landscape approach is broadly defined as a framework to integrate policy and practice for a multi-functional landscape to achieve equitable and sustainable use of land while strengthening measures to mitigate and adapt to climate change. The landscape in Karang Sidemen Village, located at the bottom of Rinjani volcano, consists of a mosaic of management regimes. This study assessed the soil profile and properties of six management regimes, namely, secondary forest, monoculture stand, agroforestry in KHDTK Rarung, agroforestry in community forest, banana-dominant landscape in Hortipark Tastura, and mix planted forest. Soil profile and pH data were collected in September 2020 from a two-dimensional soil wall (100 cm depth). Soil samples from 30 cm depth of each forest were analyzed for the soil properties (Soil Organic Carbon, Bulk Density, Soil Water Content, Litter Biomass). The results showed that the vertical pH in the soil profile is generally increasing or steady from top to bottom except for the secondary forest. The pH value ranged from 5.0 to 7. The soil colors are mostly in the yellow-red category. The soil in the six management regimes are still ideal for plant growth indicated by its low bulk density and ideal pH range for plant growth. SOC is highest in the secondary forest and lowest in the even-aged stand. SWC is highest in the secondary forest and lowest in the agroforestry in KHDTK Rarung. The litter biomass in secondary forest is two times higher than in agroforestry sites and four times higher than in banana-dominant landscape, monoculture stand and mix planted forest.